SECURITY AND DATA PROTECTION IN ARTIFICIAL INTELLIGENCE - MARKOVIĆ, Marko; SOLEŠA, Dragan (Journal of process management and new technologies, 2025)
The development of artificial intelligence contributes to the digital transformation of the entire society, improving numerous processes, automation and better decision-making. In addition to the many opportunities it offers, it also brings with it great risks in data security. The problem is further complicated by unauthorized access to data processed by artificial intelligence models, data theft, ethical dilemmas and lack of algorithm transparency. This paper analyzes artificial intelligence through different fields and the problems it can cause. A special emphasis is on the research into user attitudes, which shows us what kind of knowledge respondents have about artificial intelligence and all the risks it can cause. The results help us to see what the biggest problems regarding the use of such models are. The work provides guidelines for minimizing risks and creating problems, while dictating the trend for responsible use of artificial intelligence for legally correct purposes.
Keywords: Artificial intelligence; data security; ethical dilemmas; transparency of algorithms; security aspects